Factors to consider when designing a virtual environment to treat stress - Zaharuddin F.A.; Ibrahim N.; Rusli M.E.; Mohd Mahidin E.M.; Yusof A.M. (Springer, 2023)
Designing factors; Mental stress; Research questions; Systematic literature review; Virtual reality technology; Virtual reality